Factors influencing the rating of sonographer students' clinical performance. Issue 1 (February 2022) - Bowman, A.; Harreveld, R.B.; Lawson, C.
Abstract: Introduction: Little is known about the factors influencing clinical supervisor-assessors' ratings of sonographer students' performance. This study identifies these influential factors and relates them to professional competency standards, with the aim of raising awareness and improving assessment practice. Methods: This study used archived written comments from 94 clinical assessors describing 174 sonographer students' performance one month into their initial clinical practice (2015–6). Qualitative mixed method analysis revealed factors influencing assessor ratings of student performance and provided an estimate of the valency, association, and frequency of these factors. Results: Assessors provided written comments for 93 % (n = 162/174) of students. Comments totaled 7190 words (mean of 44 words/student). One-third of comment paragraphs were wholly positive, two-thirds were equivocal. None were wholly negative. Thematic analysis revealed eleven factors, and eight sub-factors, influencing assessor impressions of five dimensions of performance. Of the factors mentioned, 84.6 % (n = 853/1008) related to professional competencies. While 15.4 % (n = 155/1008) were unrelated to competencies, instead reflecting humanistic factors such as student motivation, disposition, approach to learning, prospects and impact on supervisor and staff. Factors were prioritised and combined independently, although some associated. Conclusion: Clinical assessors formed impressions based on student performance, humanistic behaviours and personal qualities not necessarily outlined in educational outcomes or professional competency standards. Their presence, and interrelations, impact success in clinical practice, through their contribution to, and indication of, competence. Implications for practice: Sonographer student curricula and assessor training should raise awareness of the factors influencing performance ratings and judgement of clinical competence, particularly the importance of humanistic factors. Inclusion of narrative comments, multiple assessors, and broad performance dimensions would enhance clinical assessment of sonographer student performance.